ENGINEERING GEOLOGICAL CONDITIONS OF THESSALONIKI BASIN FOR UNDERGROUND WORKS - Kokkala, A.; Marinos, V. (Bulletin of the Geological Society of Greece, 2016)
The design and construction of underground works in an urban environment, face several geological challenges. The construction of a well-structured database, able to store, manage, analyse and correlate a large amount of geological and geotechnical data, is a powerful tool towards the geological hazard assessment and the geotechnical characterisation of the formations along a tunnel. The data processed by the database are based on borehole geological information, laboratory testing, geotechnical characterisation and in situ field tests, mainly executed in the quaternary and neogene soil formations that are met along the studied area. The processing and assessment of the information, leads to the identification of useful value ranges for several physical and mechanical parameters. The study also focuses in specific areas within the basin of Thessaloniki, highlighting the in situ conditions, by the construction of longitudinal profiles. The purpose of that process, besides incorporating new data, is to provide a tool for turning data into useful information in order to estimate the geological situation and geotechnical behavior of formations in underground works.